El Niño–Southern Oscillation variability, teleconnection changes and responses to large volcanic eruptions since AD 1000. (5th February 2019) - Dätwyler, Christoph; Abram, Nerilie J.; Grosjean, Martin; Wahl, Eugene R.; Neukom, Raphael
Abstract : The El Niño–Southern Oscillation (ENSO) is the earth's dominant mode of inter‐annual climate variability. It alternates between warm (El Niño) and cold (La Niña) states, with global impacts on climate and society. This study provides new ENSO reconstructions based on a large, updated collection of proxy records. We use a novel reconstruction approach that employs running principal components, which allows us to take covariance changes between proxy records into account and thereby identify periods of likely teleconnection changes. Using different implementations of the principal component analysis enables us to identify periods within the last millennium when quantifications of ENSO are most robust. These periods range from 1580 to the end of the 17th century and from 1825 to present. We incorporate an assessment of consistency among our new and existing ENSO reconstructions leading to five short phases of low agreement among the reconstructions between 1700 and 1786. We find a consistent spatial pattern of proxy covariance during these four phases, differing from the structure seen over the instrumental period. This pattern points towards changes in teleconnections in the west Pacific/Australasian region, compared to the present state. Using our new reconstructions, we find a significant response of ENSO towards more La Niña‐like conditions 3–5 years after major volcanic events. We further show that our new reconstructions and existing reconstructions largely agree on the state of ENSO during volcanic eruptions in the years 1695 and 1784, which helps put into perspective the climatic response to these events. During all other large volcanic eruptions of the last 1000 years, there is no reconstruction coherency with regard to the state of ENSO. Abstract : This study provides new ENSO reconstructions based on a large, updated collection of proxy records. We identify the periods from 1580 to the end of the 17th century and from 1825 to present as most robust to quantify ENSO within the last millennium, and reveal disagreement among various ENSO reconstructions during five periods within 1700–1786, possibly related to teleconnection changes in the west Pacific domain. We find a significant response of ENSO towards more La Niña‐like conditions 3–5 years after major volcanic events.